The Right to Defence in Criminal Proceedings: International Law Aspects - Gutnyk, Vitalii (Teisė, 2022)
The article deals with the right to defence in criminal proceedings in accordance with international law norms. It is proved that ensuring the right to defence is one of the basic principles of criminal justice and is a prerequisite for the achievement of a fair trial. Particular attention is paid to the right to self-defence (defence in person), the right to defence through choosing legal assistance, the right to assigned legal assistance. Attention is drawn to the fact that the right to defence in the international human rights courts and the international criminal courts is based on the same principles, respectively its understanding is the same in these international courts.